2023
DOI: 10.1038/s41467-023-37140-5
|View full text |Cite
|
Sign up to set email alerts
|

In situ acid etching boosts mercury accommodation capacities of transition metal sulfides

Abstract: Transition Metal sulfides (TMSs) are effective sorbents for entrapment of highly polluting thiophiles such as elemental mercury (Hg0). However, the application of these sorbents for mercury removal is stymied by their low accommodation capacities. Among the transition metal sulfides, only CuS has demonstrated industrially relevant accommodation capacity. The rest of the transition metal sulfides have 100-fold lower capacities than CuS. In this work, we overcome these limitations and develop a simple and scalab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…16 Besides, MSs outperformed ACs because the adsorption energy of mercury on metal sulfide surfaces (reaching more than 300 kJ mol −1 ) is higher than that on carbonaceous surfaces (∼50 kJ mol −1 ), and the leachability of the adsorption products from Hg-laden MSs (∼0.005%) is much lower than that from Hg-laden ACs (∼1%). 15,22,23 Finally, for two typical flue gas components that may have detrimental effects on the Hg 0 removal performance of ACs, i.e., SO 2 and H 2 O, 24,25 MSs exhibit approximately 100% resistance to the adverse impacts of SO 2 , 26 which further supports the candidature of MSs as potential alternatives to ACs. Attributed to these favorable features, MSs-based Hg 0 sorbents have revolutionarily been stepping toward extensive application and commercialization in recent years.…”
Section: ■ Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…16 Besides, MSs outperformed ACs because the adsorption energy of mercury on metal sulfide surfaces (reaching more than 300 kJ mol −1 ) is higher than that on carbonaceous surfaces (∼50 kJ mol −1 ), and the leachability of the adsorption products from Hg-laden MSs (∼0.005%) is much lower than that from Hg-laden ACs (∼1%). 15,22,23 Finally, for two typical flue gas components that may have detrimental effects on the Hg 0 removal performance of ACs, i.e., SO 2 and H 2 O, 24,25 MSs exhibit approximately 100% resistance to the adverse impacts of SO 2 , 26 which further supports the candidature of MSs as potential alternatives to ACs. Attributed to these favorable features, MSs-based Hg 0 sorbents have revolutionarily been stepping toward extensive application and commercialization in recent years.…”
Section: ■ Introductionmentioning
confidence: 61%
“…As a thiophilic element, Hg 0 tends to combine with sulfur-based ligands and permanently deposit as mercury sulfide (HgS) through this process in nature. Valuable inspirations were thus taken from this natural process, and the discussions on the feasibility of using metal sulfides (MSs), with the surface adequately covered by sulfur, as promising alternatives to ACs for commercialized Hg 0 remediation in the postconvention era have been rising since 2016. , It was found that MSs generally possess at least 10-fold higher Hg 0 accommodation capacity than that of ACs . Besides, MSs outperformed ACs because the adsorption energy of mercury on metal sulfide surfaces (reaching more than 300 kJ mol –1 ) is higher than that on carbonaceous surfaces (∼50 kJ mol –1 ), and the leachability of the adsorption products from Hg-laden MSs (∼0.005%) is much lower than that from Hg-laden ACs (∼1%). ,, Finally, for two typical flue gas components that may have detrimental effects on the Hg 0 removal performance of ACs, i.e., SO 2 and H 2 O, , MSs exhibit approximately 100% resistance to the adverse impacts of SO 2 , which further supports the candidature of MSs as potential alternatives to ACs. Attributed to these favorable features, MSs-based Hg 0 sorbents have revolutionarily been stepping toward extensive application and commercialization in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…21−26 In comparison to other forms of mercury, Hg 0 , which is highly stable and insoluble in water, is the most difficult to remove. 27,28 Promoting the oxidation of Hg 0 is the key to improving the mercury removal efficiency. 29−33 However, as a result of significant differences in combustion processes, the release, migration, and removal mechanisms of mercury under CLC conditions are different from those under conventional conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Most mercury in solid fuels is released into the flue gas during combustion. Mercury in the flue gas can be divided into three forms: elemental mercury (Hg 0 ), oxidized mercury (Hg 2+ ), and particulate mercury (Hg p ). In comparison to other forms of mercury, Hg 0 , which is highly stable and insoluble in water, is the most difficult to remove. , Promoting the oxidation of Hg 0 is the key to improving the mercury removal efficiency. However, as a result of significant differences in combustion processes, the release, migration, and removal mechanisms of mercury under CLC conditions are different from those under conventional conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal sulfides (TMSs) are promising electrochemical energy storage materials due to large interlayer space, abundant active sites, and high theoretical capacity. Among them, MoS 2 /C nanohybrids have attracted lots of attention because of their low cost and wide availability. MoS 2 /C has a structure similar to graphene. They are stacked together by weak van der Waals forces.…”
Section: Introductionmentioning
confidence: 99%